Kajian Teknis Design Life of Mine (LOM) Tambang dengan Potensi Kerjasama Sharing Wall Project Melalui Pendekatan Analisis Kestabilan Lereng - Wahyu Wibowo; Nurhakim Nurhakim (Lambung Mangkurat University Press, 2022)
For applying good mining principles, the Minister of Energy and Mineral Resources Decree No. 1827 provides guidelines on the implementation of coal conservation, one of which is joint mining at the IUP border. Joint mining is called the Sharing Wall Project which aims to optimize the achievement of marginal reserve mining recovery. Technically, the Sharing Wall Project can only be carried out if both companies are mining simultaneously at the IUP border with the geometry parameters and policies that have been previously agreed upon. Therefore, it is necessary to have a LOM Design Option that is safe to do during the preparation process as well as to anticipate if there is no cooperation agreement. Making the LOM Design Options must take into account the analysis of slope stability and the potential amount of remaining marginal reserves. Factors that influence the results of slope stability analysis are the groundwater level and the overall slope design. The geotechnical recommendation after declaring the LOM Design Option safe is to add ground water level data and material properties in the rehandle disposal area to strengthen the next analysis. Marginal coal that is not mined at the IUP border becomes a gain when the Sharing Wall Project collaboration is carried out. Based on the calculation of reserves the Design Option LOM resulted in a total coal gain of 2.6 million tons for both companies. This means additional royalty payments to the Government from the acquisition of marginal coal reserves at the IUP border.